Is Canine Prostate-Specific Esterase a Reliable Marker for Benign Prostatic Hyperplasia Progression in Dogs? - Florin-Petrișor Posastiuc; Nicolae-Tiberiu Constantin; Guillaume Domain; Lotte Spanoghe; Ann Van Soom; Alexandru Ilie Diaconescu; Mario-Darius Codreanu (Animals)
Benign prostatic hyperplasia (BPH) is a common condition in intact male dogs, often progressing from subclinical to symptomatic stages with increasing clinical and structural impact. This study evaluated canine prostate-specific esterase (CPSE) as a biomarker for BPH progression, focusing on clinical severity, complexity, and ultrasonographic features. Seventy-one dogs were included: subclinical-BPH (n = 14), clinical-BPH (n = 26), BPH-prostatitis (n = 9), and controls (n = 22). CPSE levels, measured using a canine-specific enzyme-linked immunosorbent assay, were significantly correlated with clinical severity (ρ = 0.800, p ≤ 0.001) and complexity (ρ = 0.818, p ≤ 0.001). CPSE predicted mild (OR = 1.260, B = 0.231, p ≤ 0.001) and moderate severity (OR = 1.300, B = 0.262, p ≤ 0.001), as well as low (OR = 1.225, B = 0.203, p ≤ 0.05), moderate (OR = 1.235, B = 0.211, p ≤ 0.01), and high (OR = 1.346, B = 0.297, p ≤ 0.001) clinical complexity. CPSE showed a trend toward predicting structural alterations (OR = 1.227, B = 0.204, p = 0.069) and was associated with larger stippled areas, increased prostatic volume, and larger cysts/abscesses (all p ≤ 0.001). CPSE appears to be a promising marker for BPH progression.